The struggle against aging, a bioethical analysis (Research, Society and Development, 2021)
We live in a society that refuses to grow old. The aesthetic demands imposed by society, to be always youthful in appearance, denying or hiding the signs that the passage of time imposes, directly affect elderly people in a stigmatizing way, having their possibilities diminished by the feeling of not belonging. Objective: The objective of this article is to explore the strategies declared in the struggle against aging. It seeks to analyze the aspects that support the strategies and discuss the phenomenon of combating aging from the perspective of bioethics. Methodology: This is a qualitative research that used the public domain content available on the internet as material for analysis, which mostly aims at the aesthetic ideal. The research performed direct data collection with the researcher as the main instrument and performed Bardin's content analysis. Conclusion: Currently the strategies declared in the struggle against aging aim an aesthetic ideal, to allow the elderly to remain in the social environment. They are strategies to disguise aging or try to prevent it in an incessant search for eternal youth.